DIARY WRITING TOWARD A RECOUNT TEXT WRITING ABILITY - Kusuma, Novelia Meida; Rufinus, Albert; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted on the effect of Diary Writing was effective in teaching writing a recount text to the eighth grade students of SMPN 11 Pontianak in academic year 2017/2018. The purposes of this research is to know the effectiveness of diary writing to improve student? writing ability of a recount text. Sample of this research are Class VIII A was the experimental group and class VIII F was the control group. The experimental group given a treatment that is diary writing and the control group did not given the treatment. To know the effectiveness of diary writing the writer gave a pretest and posttest. Pretest before treatment and posttest after treatment. The students? write a diary writing with the generic structure of recount text. Diary writing and recount text is a text to tell the reader about past experience. The result of this research showed that diary writing was effective to improve students? writing ability in recount text.           Keywords : Writing, Recount text, Diary Writing